Peran Inovasi Produk dalam Meningkatkan Keunggulan Kompetitif UMKM - Nur Fitri Ayu Nandini; Winda Yuniar; Yulia Novita; Ristiliana Ristiliana (CV Muara Edukasi, 2025)
Product innovation plays an important role in helping micro, small, and medium enterprises (MSMEs) enhance their competitive advantage amid increasingly intense competition. Innovation is not limited to the creation of new products but also includes quality improvement, product variation development, packaging design renewal, and the utilization of technology to better meet consumer needs. Through these innovations, MSMEs are able to create competitive advantages in the form of product differentiation, increased value added, and the ability to maintain customer loyalty compared to competitors. In various MSME sectors such as food processing, handicrafts, and beverages, innovation strengthens product identity, enhances attractiveness, and builds positive consumer perceptions that contribute to improved market competitiveness. Meanwhile, MSMEs such as Sugar Souvenir demonstrate that innovation can also generate competitive advantages based on social and environmental values, for example through the use of recycled materials, empowerment of local labor, and collaboration with various partners to expand business networks. Overall, product innovation serves as a key strategy for MSMEs to build sustainable competitive advantage, enabling them to remain relevant, adaptive, and resilient in a constantly changing market